The Train-Line Pattern on Duplex Ultrasound Helps Differentiate Intramural Thrombus from Atheromatous Plaque in Common Carotid Artery Dissection - Ming-Hsing Chang; Yen-Yu Huang; Fang-I Hsieh; Kuan-Yu Lin; Hsu-Ling Yeh; Kai-Jing Yeh; Li-Ming Lien (Diagnostics)
Background/Objectives: Common carotid artery dissection (CCAD) can result in severe neurological sequelae; however, its diagnosis may be challenging due to consciousness disturbance and aphasia. The objective of this article is to propose a new imaging feature to assist in the identification of CCAD. Methods: This retrospective case series enrolled 139 patients with discharge diagnoses of aortic dissection who underwent carotid ultrasound during admission over a period of three years. Results: Among these patients, 23 had type A aortic dissection, and 113 had type B aortic dissection or related conditions. Notably, among the 23 patients with type A aortic dissection, eight had associated common carotid artery dissection (CCAD), and a total of nine CCAD events were identified. Meanwhile, a B-mode ultrasound revealed six double lumens with intimal flaps and three intramural thrombi. The ‘train-line’ pattern in ultrasonography was discerned by detecting a hypoechoic thickened wall, which was characterized by a margin formed by two parallel linear reflections in close proximity. This distinctive “train-line” pattern was identified in three intimal flaps and two intramural thrombi. Conclusions: While double lumens and intramural thrombus are prevalent findings, the latter may be misinterpreted as atherosclerotic plaque. The “train-line” pattern may aid in distinguishing intramural thrombus from atheromatous plaque, offering an additional diagnostic tool alongside the identification of double lumens with intimal flaps.